Dermoid cyst of the upper lip in a pediatric patient: case report - Rodrigues, Bruno Teixeira Gonçalves; Rio, Maria Ivanda Rabelo do; Kuzsminszky, Erika Castro; Romañach, Mário José; Andrade, Bruno Augusto Benevenuto de; Israel, Mônica Simões (Journal of Oral Diagnosis, 2022)
Introduction: Dermoid cyst (DC) is a slow-growing benign developmental cysts that arises from ectodermal tissue and can occur anywhere in the body, with only 34% occurring in the head and neck region, of which 6.5% are located in the mouth floor and rarely in the upper lip. It usually presents as painless, slow-growing lesion with doughy consistency and is often soft and well encapsulated - generally observed on the second to third decade of life. Objective: The objective of this article is to report a case of DC, focusing on its clinical and histopathological characteristics, and to discuss possible clinical presentations to assist in the diagnosis of this rare lesion in the oral cavity. Case Report: A 4-year-old female was referred for evaluation of an asymptomatic swelling in the left upper lip mucosa region lasting 1 year. Extraoral clinical examination showed no alterations. Intraoral clinical examination revealed the presence of a single painless well-defined nodular, sessile, non-tender swelling covered by normal oral mucosa, and located in the upper labial mucosa. An excisional biopsy was performed, and microscopic examination revealed a cystic cavity covered by orthokeratinized stratified squamous epithelium with hair follicles and sebaceous glands found within the fibrous wall. Patient recovery was uneventful and there are no signs of local recurrence in a two-year clinical follow-up. Conclusion: DC can occur anywhere in the body, but once in the oral cavity, it is rarely observed in the upper lip.